Studi Komparasi Regulasi Sertifikasi Halal oleh Majelis Ulama Indonesia (MUI) dan Badan Penyelenggara Jaminan Produk Halal (BPJPH) - Chulsum Layyinatul Chasanah; Shofiyullah Muzammil (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
Halal products are increasingly in demand by many people, not only in the national market but also in the international market. Indonesia has experienced an increase in the consumption rank of halal products from year to year. One of the indicators is the implementation of halal certificates. Halal certificates cannot be issued just like that without procedures and checks from the authorities. However, looking at the dynamics, halal certificates have experienced developments from time to time. These changes can be seen after the existence of Law No. 33 of 2014 concerning Halal Product Guarantee. The formulation of this problem is how is the comparison between the regulation of halal certificates by MUI and BPJPH? The purpose of this study is to determine the comparison of halal certificate regulations by MUI and BPJPH, namely before and after the issuance of the JPH Law. This research uses the Library study method with various sources that support the object of research. The primary data source of this research is Law No.33 of 2014, MUI Fatwa, and its official website. Secondary data sources are from journals, theses, and related theses. The result of this research is that there are similarities and differences between the regulation of halal certificates by MUI and BPJPH. The difference is not only in the content of the regulation, but also in the halal logo issued. This logo is not just a picture, but more than that, it has a deep philosophy. Keywords: BPJPH, Halal, Certificate, MUI Halal products are increasingly in demand by many people, not only in the national market but also in the international market. Indonesia has experienced an increase in the consumption rank of halal products from year to year. One of the indicators is the implementation of halal certificates. Halal certificates cannot be issued just like that without procedures and checks from the authorities. However, looking at the dynamics, halal certificates have experienced developments from time to time. These changes can be seen after the existence of Law No. 33 of 2014 concerning Halal Product Guarantee. The formulation of this problem is how is the comparison between the regulation of halal certificates by MUI and BPJPH? The purpose of this study is to determine the comparison of halal certificate regulations by MUI and BPJPH, namely before and after the issuance of the JPH Law. This research uses the Library study method with various sources that support the object of research. The primary data source of this research is Law No.33 of 2014, MUI Fatwa, and its official website. Secondary data sources are from journals, theses, and related theses. The result of this research is that there are similarities and differences between the regulation of halal certificates by MUI and BPJPH. The difference is not only in the content of the regulation, but also in the halal logo issued. This logo is not just a picture, but more than that, it has a deep philosophy.